2014
DOI: 10.1155/2014/595837
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the Anesthetic Management of Intraoperative Rupture of Intracranial Aneurysm

Abstract: Despite great advancements in the management of aneurysmal subarachnoid hemorrhage (SAH), outcomes following SAH rupture have remained relatively unchanged. In addition, little data exists to guide the anesthetic management of intraoperative aneurysm rupture (IAR), though intraoperative management may have a significant effect on overall neurological outcomes. This review highlights the various controversies related to different anesthetic management related to aneurysm rupture. The first controversy relates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 77 publications
0
15
0
1
Order By: Relevance
“…Smoking appears to be associated with increased chances of IORin previous studies also. 6 No other identifiable risk factor was seem to be associated. We found that in few cases (9 patients), there were dense adhesions in the sylvian fissure and peri aneurysm.…”
Section: Discussionmentioning
confidence: 96%
“…Smoking appears to be associated with increased chances of IORin previous studies also. 6 No other identifiable risk factor was seem to be associated. We found that in few cases (9 patients), there were dense adhesions in the sylvian fissure and peri aneurysm.…”
Section: Discussionmentioning
confidence: 96%
“…In these cases, the perioperative anesthetic management can have a significant effect on global neurological results by monitoring many factors, including the induction of anesthesia, the presence or absence of burst suppression, use of volatile agents/muscle relaxants, hemodynamic parameters, and temperature. In any case, these parameters must be assisted by intraoperative neurophysiological monitoring with EEG and evoked potentials [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A gradual increase in blood pressure accompanied by a precipitous drop in heart rate may signal an IOR. Changes in the neurological exam may be difficult to assess given GA; however, raised intracranial pressure and herniation can be recognized clinically with a unilateral change in pupil size [12]. The anesthetic care of IOR is complex, and aneurysm rupture in a closed skull carries a worse prognosis due to elevation in intracranial pressure impairing cerebral perfusion [13].…”
Section: Discussionmentioning
confidence: 99%